Analisis Pengetahuan Investasi, Risiko Investasi Dan Modal Minimal Terhadap Minat Investasi Di Pasar Modal (Studi Kasus Mahasiswa Universitas PGRI Palembang) - Puja Lestari; Hendry Saladin; O. Oktariansyah (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2024)
This study aims to test the hypothesis of the effect of investment knowledge, investment risk and minimum capital on investment interest in the capital market. The population of this study were all students of PGRI University Palembang. The sampling technique using the Yamane formula so that the sample amounted to 378 respondents. The sampling technique used random sampling method and data collection using a questionnaire. This research uses quantitative methods with the help of SPSS 22 as a measuring tool. The results of this study show that simultaneously the significant value obtained is 0.000, which is smaller than 0.05, so H4 is accepted simultaneously investment knowledge, investment risk and minimum capital have a significant effect on investment interest in the capital market, then partially investment knowledge affects investment interest with a significant value of 0.039 <0.05, so H1 is accepted. Investment risk has a significant effect on investment interest with a significant value of 0.000 <0.05, so H2 is accepted. And minimum capital also partially affects investment interest with a significant value of 0.000 <0.05, so H3 is also accepted.